2019
DOI: 10.3390/cells8121557
|View full text |Cite
|
Sign up to set email alerts
|

Non-Redundant and Overlapping Oncogenic Readouts of Non-Canonical and Novel Colorectal Cancer KRAS and NRAS Mutants

Abstract: RAS oncogene family members are molecular switches of signaling pathways that control cell growth, proliferation, differentiation, and survival. In colorectal cancer, Kirsten-RAS (KRAS) and neuroblastoma-RAS (NRAS) are the commonly mutated isoforms. Activating mutations in RAS result in cellular transformation independent of upregulated epidermal growth factor receptor (EGFR)-initiated signaling. The present study characterized the functional consequences of non-canonical/novel KRAS and NRAS mutants identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This study reveals the first and unexpected causal link between KRAS or BRAF mutations and hepatic vascular cavernomas. Mutations in RAS, the first human oncogene, and BRAF genes drive ∼30% of human tumors ( Alcantara et al, 2019 ; Hunter et al, 2015 ; Lu et al, 2016 ; Smith et al, 2013 ; Der et al, 1982 ; Zhong et al, 1999 ; Davies et al, 2002 ; Thomas et al, 2007 ), yet no reports describe RAS or RAF mutations in hepatic cavernous hemangiomas, the most common benign tumor of the liver. We identified somatic activating KRAS and/or BRAF mutations in human hepatic tissue samples with sporadic hemangioma lesion ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals the first and unexpected causal link between KRAS or BRAF mutations and hepatic vascular cavernomas. Mutations in RAS, the first human oncogene, and BRAF genes drive ∼30% of human tumors ( Alcantara et al, 2019 ; Hunter et al, 2015 ; Lu et al, 2016 ; Smith et al, 2013 ; Der et al, 1982 ; Zhong et al, 1999 ; Davies et al, 2002 ; Thomas et al, 2007 ), yet no reports describe RAS or RAF mutations in hepatic cavernous hemangiomas, the most common benign tumor of the liver. We identified somatic activating KRAS and/or BRAF mutations in human hepatic tissue samples with sporadic hemangioma lesion ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Riquelme et al also confirmed that not all oncogenic K-Ras mutants activate and enhance MAPK signaling by showing that the level of phospho-MEK1/2 is increased in NSCLC cells harboring the KRAS G12C and KRAS G12D mutations but decreased in cells harboring the KRAS G12R and G12S [3]. By contrast, a recent study using NIH3T3 cells showed that KRAS G12S-expressing cells had elevated p-ERK levels, suggesting that this mutant in this setting exerts its oncogenic phenotype via MAPK signaling [6].…”
Section: The Mapk Pathwaymentioning
confidence: 67%
“…What has been reported is that cells with A59T, as with a select few other forms of KRAS and NRAS , have higher rates of cell proliferation and migration in vitro; furthermore, A59T deregulates extracellular signal-related kinase (ERK) and the downstream target ETS transcription factor ELK1. Based on reports to date, it is clear that the role of A59T as a molecular regulator is quite different than other, more well-characterized and more common forms of RAS [ 11 ]. The A59T mutation reduces GTPase activity fivefold [ 12 ] and doubles the nucleotide exchange rate compared to wild-type RAS .…”
Section: Discussionmentioning
confidence: 99%